PEMILIHAN FINTECH PAYMENT QRCODE UNTUK PELANGGAN MENGGUNAKAN TOPSIS - Rofiah, Syahbaniar; Setiyadi, Didik; Retnoningsih, Endang; Sandradewi, Kumaratih (ISTEK WIDURI, 2023)
Payment is inseparable from technology so it is fast in making transactions in real time. Payment is the most important stage in sales. Sales success can be obtained from the service process, both from the process of entering sales transactions to payment transactions. Problems that occur in transactions using the QRCode fintech payment are, it takes too long to read the QRCode, an error occurs when reading the QRCode, has made a payment but it is not detected. The aim of the research is to help service providers fix deficiencies that occur and help customers choose a QRCode fintech that is safe and fast to use. This research seeks QRCode fintech payment recommendations for customers using the Technique For Order Preference by Similarity of Ideal Solution (TOPSIS) with 6 alternatives, namely Sakuku, Link Aja, Gopay, Dana, Shopeepay and OVO. Then the 6 criteria consist of: C1 = real time, C2 = user friendly, C3 = payment, C4 = security, C5 = feature diversity, and C6 = merchant. The results obtained by Gopay obtained the highest score of the other 6 alternatives, namely 0.9208, which was chosen as the best QRCode fintech payment recommendation.